Knowledge Intermediation Strategies: Novel Evidence from Canada - Traoré, Namatié; Amara, Nabil (My University, 2016)
This study investigates i) difference in knowledge intermediation strategies among knowledge and technology transfer organizations (KTTOs) and ii) the factors that explain such differences. It uses data from 212 Canadian KTTOs. When knowledge delivery and integration capabilities dimensions of knowledge intermediation are simultaneously accounted for, four categories of KTTOs emerge, namely, 1) knowledge stores; 2) knowledge match providers; 3) knowledge integrators and; 4) knowledge brokers. This heterogeneity results in a differentiation in KTTOs' service delivery strategies. A high absorptive capacity and an effective customer knowledge management strategy are conducive to richer service content and custom-made solutions. Larger knowledge intermediaries suffer from internal organizational stickiness that prevents them from delivering custom-made services. KTTOs with a low degree of formalization and centralization in decision-making are likely to adopt intermediation strategies aimed at reaching the largest possible number of users. Some managerial and public policy implications are drawn.